2021
DOI: 10.1093/jac/dkab122
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo synergistic effects of tigecycline combined with aminoglycosides on carbapenem-resistant Klebsiella pneumoniae

Abstract: Objectives Carbapenem-resistant Klebsiella pneumoniae (CR-KP) infections represent severe threats to public health worldwide. The aim of this study was to assess potential synergistic interaction between tigecycline and aminoglycosides via in vitro and in vivo studies. Methods Antibiotic resistance profiles and molecular characteristics of 168 CR-KP clinical isolates were investigated by susceptibility testing, PCR and MLST. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Moreover, synergy was demonstrated between tigecycline and aminoglycosides (34)(35)(36), colistin and levofloxacin (37,38), fosfomycin and cephalosporins (31) or doripenem (39,40) against K. pneumoniae. Principe et al also reported synergy between tigecycline and levofloxacin against Acinetobacter baumanii strains (41).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, synergy was demonstrated between tigecycline and aminoglycosides (34)(35)(36), colistin and levofloxacin (37,38), fosfomycin and cephalosporins (31) or doripenem (39,40) against K. pneumoniae. Principe et al also reported synergy between tigecycline and levofloxacin against Acinetobacter baumanii strains (41).…”
Section: Discussionmentioning
confidence: 99%
“…Carbapenems have been widely used to against MDR Enterobacteriaceae . Unfortunately, with the increased use, carbapenem-resistant Enterobacteriaceae has been emerged and spread rapidly, especially in K. pneumoniae ( Ni et al., 2021 ). Infections induced by CRKP have been considered a great challenge in clinical practices ( Agyeman et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we tested the susceptibility of 168 non-duplicate CR-KP clinical strains collected from different patients during June 2014–December 2018 in four tertiary hospitals in Beijing, China ( Ni et al, 2021 ). Among them, 98 CR-KP strains from three tertiary hospitals were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The time-kill assays for colistin monotherapy and combination therapy were performed as previously described ( Ni et al, 2021 ). The concentration of colistin and other antibiotics used in time-kill assays was 1 × MIC of each tested strain that was obtained from the susceptibility testing.…”
Section: Methodsmentioning
confidence: 99%